Pengaruh Perilaku Belajar, Kecerdasan Intelektual, Kecerdasan Emosional, Kecerdasan Spiritual, dan Kecerdasan Sosial terhadap Pemahaman Akuntansi (Studi Kasus Mahasiswa Program Studi Akuntansi Universitas Muhammadiyah Surakarta) - Santi Utami; Noer Sasongko (Neolectura, 2021)
This study aims to analyze the effect of learning behavior, intellectual intelligence, emotional intelligence, spiritual intelligence, and social intelligence on accounting understanding. More specifically, this study aims to explore several factors such as learning behavior, intellectual intelligence, emotional intelligence, spiritual intelligence, and social intelligence. In this study the authors use the type of quantitative research so that the significance of the relationship between the variables studied will be obtained. The data of this study used primary data containing questions in the form of a questionnaire measured using a Likert scale, which was distributed to students of the Accounting Study Program at Muhammadiyah University of Surakarta batch 2017, and obtained a sample of 80 students, while for this research method the Multiple Linear Regression method was used. to test the effect between the variables. The results of this test indicate that Intellectual Intelligence, Spiritual Intelligence, and Social Intelligence have a negative effect on Accounting Understanding. Meanwhile, Learning Behavior and Emotional Intelligence have a positive effect on Accounting Understanding. In the end, based on the results of this study, it shows that Learning Behavior and Emotional Intelligence have an effect on Accounting Understanding.